Metal Soaps in Art Conservation and Research - Casadio, Francesca; Keune, Katrien; Noble, Petria; Van Loon, Annelies; Hendriks, Ella; Centeno, Silvia A.; Osmond, Gillian (Cultural Heritage Science, 2019)
This go-to reference work surveys the current state of knowledge in the field of metal soap-related degradation phenomena in art works. It contains detailed descriptions and images of the different phenomena and addresses the practical aspects of soap formation, preventive conservation, and treatment. The occurrence of metal soaps is one of the defining issues in the conservation of painted surfaces, and one that presently leaves innumerable open questions. It is estimated that around 70% of paintings in museum collections are affected by some form of metal soap-related degradation. In recent years, significant advances have been made in the detection and characterization of these compounds through interdisciplinary approaches including conventional spectroscopy and microscopy as well as emerging synchrotron-based techniques. This book for the first time captures a panoramic overview of the state of knowledge of metal soaps related to both scientific analysis and implications for conservation and treatment. It also critically examines open questions. The book is accessible to audiences with varied backgrounds (e.g. conservators, students of conservation science) while simultaneously presenting the technical details indispensable for academics and researchers active in this field.